Penggunaan Ragam Bahasa Bugis Pada Situasi Pemilihan Umum Tahun 2019 : Kajian Etnososilinguistik - Nur Rahmi; Hj. Ratnawati Umar; Muhlis Muhlis; Muliana Muliana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2021)
Abstract: The Use of Bugis Language Variety in the 2019 General Election Situation9 : Ethnosociological Studies. This study aims to describe the variety of bugis language based on the level of social status and the level of poverty in the 2019 election situation using ethnosocisilinguistic studies. Public conversations in this situation are the source of data in this study and data obtained from the results of conversations in the form of phrases, sentences, and topics of discussion in the 2019 general election situation. The methods used in the collection are observation, recording and recording techniques, listening techniques free to engage and interviews. This study shows the use of bugis language variety in the 2019 general election situation in the discovery of bugis language ragama based on familiarity with interlocutors, namely the variety of relaxed, familiar, and official languages. In the 2019 general election, there are words used by the public that do not match their true meaning.